Effects of nano-emulsion preparations of tocopherols and tocotrienols on oxidative stress and osteoblast differentiation - Song, Liang-Song; Zhang, Zhi-Xin; Wang, Yang; Liu, Yang; Zhang, Rui; Lu, Lai-jin (Archives of Biological Sciences, 2017)
Tocopherols and tocotrienols are two groups of compounds in the vitamin E family, of which the tocopherols are widely used as antioxidant dietary supplements. Recent studies have shown mixed observations for tocopherol functions in bone homeostasis. We have evaluated the potency of suspension- and nano-emulsion formulation-based delivery of different vitamin E family members in lipopolysaccharide (LPS)-induced oxidative stress and osteoblast differentiation. Our results showed the both tocopherols and tocotrienols could reduce oxidative stress as evaluated by the levels of reactive oxygen species (ROS). Their effects were enhanced when applied in the nano-emulsion mode of delivery due to increased bioavailability. In addition, our results showed that tocotrienols increased osteoblast differentiation, while tocopherols showed reduced osteoblast differentiation, which may be due to their differential effects on SMAD and p65 signaling. Together, these findings indicate that tocotrienols delivered through nano-emulsion exhibit superior antioxidant properties and osteoblast differentiation, and could serve as a better alternative to tocopherol-based vitamin E supplements. DOI: 10.2298/ABS160208090S Received: February 8, 2016; Revised: March 18, 2016; Accepted: April 5, 2016; Published online: October 10, 2016 Song LS, Zhang ZX, Wang Y, Liu Y, Zhang R, Lu LJ. Effects of nano-emulsion preparations of tocopherols and tocotrienols on oxidative stress and osteoblast differentiation. Arch Biol Sci. 2017;69(1):149-56.